The complete chloroplast genome sequence and phylogenetic analysis of the medicinal plant Lysimachia hemsleyana - Ying, Zhiqi (Mitochondrial DNA B Resour, 2019)
Lysimachia hemsleyana Maxim. is an important medical plant in the Family Primulaceae. In this study, we determined the complete chloroplast genome of L. hemsleyana. It is 155,618 bp in length, containing a large single copy (LSC) region of 85,615 bp, a small single copy (SSC) region of 17,861 bp, which were separated by a pair of inverted repeat (IR) regions of 26,071bp. The complete chloroplast genome of L. hemsleyana encoded a total of 134 genes, including 89 protein-coding genes with the pseudogene of ycf1, 8 ribosomal RNA genes and 37 transfer RNA genes. Phylogenetic analysis revealed that L. hemsleyana was most closely related to the Korea endemic plant Lysimachia coreana with high bootstrap support value. This work provides basic molecular information that would be useful for further investigation on conservation genetics and evolutionary relationships of L. hemsleyana.